NADH Dehydrogenases in Pseudomonas aeruginosa Growth and Virulence - Torres, Angela; Kasturiarachi, Naomi; DuPont, Matthew; Cooper, Vaughn S.; Bomberger, Jennifer; Zemke, Anna (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa is an opportunistic human pathogen with a complex respiratory chain. The bacterium is predicted to express three NADH:ubiquinone oxidoreductases (NDH-1, NDH-2 and Nqr). We created deletions strains of the predicted NADH:ubiquinone oxidoreductases alone, and in combination to determine the respective roles of the NADH dehydrogenases in growth and virulence. NDH-1 and NDH-2 were largely redundant under aerobic conditions. Aerobic NADH dehydrogenase enzymatic activity assay was lost with deletion of both NDH-1 and NDH-2. Under anaerobic conditions, NDH-1 was required for robust growth, and overexpression of NDH-2 rescued the NDH-1 anaerobic growth defect in rich media. There was not compensatory upregulation of NDH-2 under anaerobic conditions in NDH-1 deletion strains. To test which genes were required for in vivo virulence, we used both an insect and plant disease model. In the Galleria mellonella model, neither deletion of NDH-1 nor NDH-2 led to a change in median lethal dose, although death occurred more slowly in the NDH-1 deletion infections. In a lettuce model of virulence, loss of NDH-1 caused a decrease in recovered viable bacteria and a decrease in visual tissue damage. The compound deletion of NDH-1/NDH-2 causes a severe growth defect, both under aerobic and anaerobic conditions, and was avirulent in a lettuce model. Together, these results demonstrate the redundancy of the P. aeruginosa respiratory chain at the NADH dehydrogenase level in aerobic growth and virulence.